Austenitemeter – Mössbauer spectrometer for rapid determination of residual austenite in steels. (January 2019) - Pechousek, Jiri; Kouril, Lukas; Novak, Petr; Kaslik, Josef; Navarik, Jakub
Highlights: Application of backscattering Mössbauer spectroscopy. Fast nondestructive determination of residual austenite content in steels. Rapid and reproducible measurement technique. Resulted values compared with those obtained by XRD method. Paramagnetic and magnetic phases (austenite – ferrite) well distinguished. Abstract: In this note we describe an application of backscattering 57 Fe Mössbauer spectroscopy for determination of the austenite content in steels, where the surface analysed thickness is ∼20 µm. The method enables rapid determination of the residual austenite in the sample, i.e. within 10–20 min with a sufficient accuracy. Calculations using different f -factors for austenite and ferrites are also adopted. Standard regime of the analysis allows determining an austenite-to-ferrite ratio with a high precision after several hours or few days of measurement for laboratory research or quality control purposes. The method demonstrates high efficiency and more sensitive results of the analysis, i.e. compared with the XRD method. Statistical quality of the spectra which affects the measurement accuracy (±1%) with detection limit of rapid method (2–3% austenite) together with noise occurrence is evaluated.